2018
DOI: 10.1159/000488216
|View full text |Cite
|
Sign up to set email alerts
|

Current Controversies in the Management of Diverticulitis: A Review

Abstract: Background: Symptomatic diverticular disease is challenging for patients, clinicians and health services. The prevalence increases with age and BMI and as such, the burden of this disease is set to increase with higher rates of acute presentations already documented. The natural history of recurrent episodes, complications and symptom progression is not fully understood. Furthermore, medical and surgical management strategies are under constant appraisal, debate and evolution. Methods: A review of the contempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
6
0
2
Order By: Relevance
“…Another important question remains whether a primary anastomosis should be performed or a Hartmann procedure subsequently. 33 There are several studies supporting the use of either type of intervention [34][35][36] but how the risk-benefit ratio would be altered when factoring in MS is not clear and there is a lack of randomized trials addressing this specific question.…”
Section: Discussionmentioning
confidence: 99%
“…Another important question remains whether a primary anastomosis should be performed or a Hartmann procedure subsequently. 33 There are several studies supporting the use of either type of intervention [34][35][36] but how the risk-benefit ratio would be altered when factoring in MS is not clear and there is a lack of randomized trials addressing this specific question.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Nally and Kavanagh [1], in a systematic review and meta-analysis, Sharma et al [2] found a pooled prevalence of colorectal cancer of 0.7% (95% CI 0.3-1.4%) in 1,497 patients (8 studies) with uncomplicated diverticulitis who underwent endoscopy. In a systematic review and meta-analysis performed this year, we found a pooled prevalence of colorectal cancer of 1.3% (95% CI 0.1-2.0%) among 3,834 patients (15 studies) with uncomplicated episodes [3].…”
Section: Dear Editormentioning
confidence: 86%
“…We read with interest the review article by Nally and Kavanagh [1] about the current controversies in the management of diverticulitis. In a section about follow-up colonoscopy, the authors recommended that endoscopic evaluation be performed after an episode of complicated diverticulitis to rule out colorectal cancer, but considered the indication for colonoscopy to be debatable in patients with uncomplicated episodes.…”
Section: Dear Editormentioning
confidence: 99%
“…Considerando esta realidad, la tendencia actual es un abordaje menos invasivo para la DC; varios autores y algunas guías clínicas dan cuenta de esta afirmación [5][6][7][8][9] . Una situación especial constituye la DA perforada asociada a neumoperitoneo y/o burbujas extracolónicas.…”
Section: Discussionunclassified
“…El tratamiento óptimo de la diverticulitis aguda complicada es materia de debate, si bien la mayoría de las guías clínicas recomienda la sigmoidectomía de urgencia, la tendencia actual es evitar la emergencia quirúrgica a través de terapias menos invasivas con un claro beneficio en morbimortalidad [5][6][7][8][9] . En este contexto publicaciones recientes plantean que el manejo no quirúrgico de pacientes con diverticulitis perforada con aire extraluminal (DPA) es una alternativa terapéutica controversial, que en casos seleccionados puede ofrecer buenos resultados y evitar la necesidad de una ostomía [10][11][12][13][14][15] .…”
Section: Introductionunclassified